Asesmen Penalaran Inch - Susanti, Try (Institut Agama Islam Negeri Imam Bonjol Padang, 2014)
The article aims to describe Inch reasoning which becomes a process to collect the evidences consciously and to relate between knowledge and experience in order to explain what has been seen, thought, and concluded. Thus, critical thinking becomes one of reasoning types. It is also a process for someone to answer difficult questions which cannot be answered in time rationally. There were eight functions that cannot be separated each other and become the indicators of critical thinking. They are Question at issue, Purpose, Information, Concepts, Assumptions, Points of View, Interpretation and inference, Implication and consequences. Therefore, it is suggested for science teacher to understand the Inch reasoning which can be implemented in their assessment.Copyright © 2014 by Al-Talim All right reservedDOI: 10.15548/jt.v21i1.74